Elastic Resistance Effectiveness on Increasing Strength of Shoulders and Hips. Issue 4 (April 2019) - Picha, Kelsey J.; Almaddah, Muataz R.; Barker, Jordan; Ciochetty, Tavis; Black, W. Scott; Uhl, Tim L.
Abstract : Abstract: Picha, KJ, Almaddah, MR, Barker, J, Ciochetty, T, Black, WS, and Uhl, TL. Elastic resistance effectiveness on increasing strength of shoulders and hips. J Strength Cond Res 33(4): 931–943, 2019—Elastic resistance is a common training method used to gain strength. Currently, progression with elastic resistance is based on the perceived exertion of the exercise or completion of targeted repetitions; exact resistance is typically unknown. The objective of this study was to determine whether knowledge of load during elastic resistance exercise will increase strength gains during exercises. Participants were randomized into 2 strength training groups, elastic resistance only and elastic resistance using a load cell (LC) that displays force during exercise. The LC group used a Smart Handle (Patterson Medical Supply, Chicago, IL, USA) to complete all exercises. Each participant completed the same exercises 3 times weekly for 8 weeks. The LC group was provided with a set load for exercises, whereas the elastic resistance only group was not. The participant's strength was tested at baseline and program completion, measuring isometric strength for shoulder abduction (SAb), shoulder external rotation (SER), hip abduction (HAb), and hip extension (HEx). Independent t -tests were used to compare the normalized torques between groups. No significant differences were found between groups. Shoulder strength gains did not differ between groups (SAb p > 0.05; SER p > 0.05). Hip strength gains did not differ between groups (HAb p > 0.05; HEx p > 0.05). Both groups increased strength because of individual supervision, constantly evaluating degree of difficulty associated with exercise and providing feedback while using elastic resistance. Using an LC is as effective as supervised training and could provide value in a clinical setting when patients are working unsupervised.